Increased pain sensitivity but normal pain modulation in adolescents with migraine. Issue 5 (May 2019) - Nahman-Averbuch, Hadas; Leon, Eric; Hunter, Benjamin M.; Ding, Lili; Hershey, Andrew D.; Powers, Scott W.; King, Christopher D.; Coghill, Robert C.
Abstract : Abstract: Inhibitory pain modulation has been reported to be deficient in adults across different types of chronic pain, including migraine. To determine whether a similar phenomenon occurs in youth, we performed a quantitative sensory testing investigation in adolescents with migraine (N = 19). These patients were compared to healthy adolescents with (Fam-His; N = 20) or without (Healthy; N = 29) a family history of migraine (eg, first-degree relative with migraine). Subjects were first familiarized with the stimuli and visual analogue rating scales using graded noxious stimuli (0°C, 43-49°C range). These data were used to explore potential pain sensitivity differences between the groups. Pain inhibition was assessed by conditioned pain modulation (CPM), which used both suprathreshold heat pain (heat CPM) and pressure pain thresholds (pressure CPM) as the test stimuli before and during cold-water immersion (8°C). In response to the graded heat stimuli, Fam-His participants reported higher pain intensity ratings compared with patients with migraine, who in turn reported higher pain intensity ratings than the healthy controls (F = 3.6, [df = 2, 459], P = 0.027). For heat and pressure CPM, there was no significant group difference in the magnitude of CPM responses. Thus, adolescents with migraine and healthy adolescents have similar inhibitory pain modulation capability, despite having marked differences in pain sensitivity. Although Fam-His participants are asymptomatic, they demonstrate alterations in pain processing, which may serve as markers for prediction of migraine development. Abstract : Supplemental Digital Content is Available in the Text.Patients with migraine and healthy adolescents with familial migraine history show increased pain sensitivity to noxious heat stimuli relative to healthy adolescents without familial migraine history.